Mechanism research of type I reactive oxygen species conversion based on molecular and aggregate levels for tumor photodynamic therapy - Youqin Xu; Yili Xie; Qing Wan; Jianwen Tian; Jing Liang; Jianlong Zhou; Mu Song; Xinke Zhou; Muzhou Teng (Aggregate)
Abstract Type I photosensitizers (PSs) with the ability to generate reactive oxygen species (ROS) containing superoxide anion and hydroxyl radical have promising application potential for treating hypoxia tumors, but the deep mechanism of type II ROS converts to the type I ROS in the PSs is still unclear, it is urgent to reveal influencing factors about inducing type I ROS generation. Herein, six PSs with aggregation‐induced emission properties, which were fabricated with the same electronic acceptor but different electronic donors and “π‐bridge”, have been successfully prepared to explore the influencing mechanism of generating superoxide anion and hydroxyl radical from organic PSs. Experimental results discovered two factors containing molecular structure and aggregated environment could decide the ROS efficiency and types of PSs. On the level of designing molecular structure, we discovered that “π‐bridge” with a lower energy level of the lowest triplet state could be beneficial for triggering the production of superoxide anion, and electronic donor of triphenylamine was an important factor in producing hydroxyl radical than another donor of dimethylamine. On the level of designing aggregates of PS‐based polymeric nanoparticles, bovine serum albumin could improve largely the generation efficiency of superoxide anion. Due to the satisfactory ROS efficiency and better biocompatibility, synthetic PSs showed excellent photodynamic therapy outcomes in vitro/vivo.